Strategi Pelayanan Misi Kontekstual Terhadap Generasi Z Yang Percaya Dengan Memanfaatkan Teknologi Informasi Dan Komunikasi - Oka Astawa; Ayu Rotama Silitonga; Brian Marpay (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2023)
Generation Z's tendency to leave the church could occur when the church does not answer the needs and accommodate the generation’s perpectuve . Therefore, mission services to generation Z need to be carried out contextually, requiring services that suit their needs. Contextual mission services must develop the right